Mathematical modeling and trajectory planning of hand finger movements - Rahman, Md. Mozasser; Choudhury, Tasnuva Tabashhum; Sidek, Shahrul Na'im; Awang, Amjad (2014)
This paper presents a mathematical model of trajectory during movement of human hand finger. Mathematical models of finger’s movement are necessary to control the finger of prosthetic hands, rehabilitation platform, and hand of cooperative robots. A simple platform is constructed with flexi force sensor and data acquisition circuit. Trajectories are calculated from the position data of the finger movement. Movement with various speed of the finger are maintained. Finally, Curve Fitting Toolbox of MATLAB is used to derive the mathematical model of finger trajectory. The obtained result could be beneficial to design the controller of the finger of prosthetic hands, rehabilitation platform, and hand of cooperative robots.